Final preparations for peak competitions: observations from the 2009 IAAF World Championships in athletics - Killing, W.; Hutt, E.; May, J.; Peter, J.; Pottel, R.; Ritschel, M.; Schult, J.; Zaar, A. (New Studies in Athletics, 2014)
ABSTRACT Classic training methodology tells us that there is little athletes can do in the four to ten days before a competition to improve their performance level. But what are the effects, positive or negative, of activities in the period after the last hard training session? From the practical point of view, what is the ideal structure for the final preparations, and even for the warm-up on the day of the competition itself? This article, adapted from a more extensive report of a project conducted under the auspices of the German Athletics Federation (Deutscher Leichtathletik-Verband - DLV) addresses these questions with an informal compilation of observations of world-class athletes going about their preparations for the 2009 IAAF World Championships in Athletics. After outlining the methodology used, the authors present observations of interest to athletes, coaches and team managers preparing for a peak competition. These are supplemented by briefcase studies of well-known athletes in each of the main event groups.